APLIKASI PUPUK TERPADU TERHADAP KARAKTER AGRONOMI TANAMAN OBAT BAWANG DAYAK (Aleutherine bulbosa Merr.) DI LAHAN TERBATAS - Darnawi, Darnawi; Setiawati, Evi; Darini, Maria Theresia; Ihsan, Ihsan; Sudrajad, Ig. S. (Fakultas Pertanian Universitas Janabadra, 2025)
This research aimed to determine the effect of a combination of organic fertilizer and synthetic fertilizer on the growth and yield of Dayak onion plant. The research was carried out in a garden in Berbah, Sleman Special Region of Yogyakarta, at an altitude of ± 194 m above sea level, the average rainfall is 145 mm year-1 and the temperature is between (24 -32) °C. The research is arranged in a Factorial Completely Randomized Design (3 x 4) 3 = 36 units, each unit consists of 8 plant polybags, 4 plants as sample plants. The first factor is three levels of source organic fertilizer: cow manure (P1), goat manure (P2) and household waste compost (P3). The second factor is four levels of dose of urea : 0 (N0), 4 (N1), 6 (N2) and 8 (N3) g polybag-1. Observations variables included components of growth and yield of Dayak onions. Analysis of variance used diversity analysis at the 5% level significant, followed by Duncan's Multiple Range Test at the 5% level significant. The result of the research showed that there was an interaction between the source of organic fertilizer and the dose of urea fertilizer on the variable components of growth and yield of Dayak onion plant. The best growth of dayak onion plant was obtained from a combination of goad manure with urea fertilizer at a dose of 6 g polybag-1, while high tuber weight was obtained from combination of compost fertilizer and urea at a dose 4 g polybag-1.